EEG Sinyalinin Anestezi Sırasındaki Topografik ve Zamansal İzge Analizi - Uslu, Atilla; Cebeci, Bora; Erdoğan, Ezgi T.; Kaşıkçı, Itır; Seyhan, Tülay Ö.; Akan, Aydın; Demiralp, Tamer; GÜRKAN, GÜRAY (IEEE, 2018)
Bu çalışmada EEG sinyalinin anestezi altındaki izgesel değişimi, zamansal ve uzaysal olarak incelenmiştir. Bu amaçla kullanılan yöntemler arasında, günümüz anestezi derinliği takip cihazlarının da kullandığı bilinen SEF-90, α-β bandı güç oranları ve izgesel entropi yer almaktadır. Ayrıca doğrusal olmayan sistemlerin analizinde kullanılan Higuchi fraktal boyutu da karşılaştırma olarak incelenmiştir. Uzaysal analiz sonucunda, normal bireylerde oksipital bölgede görülen baskın alfa aktivitesinin artan anestezi derinliği ile frontal bölgeye kaydığı doğrulanmış ve ilgili topografik gösterimler sunulmuştur.

In this study, we present the spatial and temporal evolution of EEG signal spectrum under anaesthesia. Studied features include SEF-90, α-β power ratios, spectral entropy that are known to be used in commercially available depth of anaesthesia monitors. As an additional and comparing feature, we also present Higuchi fractal dimension that is used for analysis of non-linear systems. By means of spatial analysis, we verified the shift of occipitally dominant alpha activity to frontal regions and demonstrated corresponding topographic plots.
Topographic and temporal spectral analysis of EEG signals during anaesthesia
Keywords: Spectral analysis; Electroencephalography; electroencephalography; entropy; fractals; medical signal processing; spectral analysis; topographic analysis; temporal spectral analysis; EEG signals; anaesthesia; α-β power ratios; spectral entropy; spatial evolution; temporal evolution; Higuchi fractal dimension; occipitally dominant alpha activity